2015
DOI: 10.1016/s1470-2045(14)71182-9
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib for previously untreated and relapsed or refractory chronic lymphocytic leukaemia with TP53 aberrations: a phase 2, single-arm trial

Abstract: Summary Background Patients with chronic lymphocytic leukaemia (CLL) with TP53 aberrations respond poorly to first-line chemoimmunotherapy resulting in early relapse and short survival. We investigated the safety and activity of ibrutinib in previously untreated and relapsed or refractory CLL with TP53 aberrations. Methods In this investigator-initiated, single-arm phase 2 study we enrolled eligible adult patients with active CLL with TP53 aberrations at the National Institutes of Health Clinical Center (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
264
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(289 citation statements)
references
References 29 publications
17
264
0
8
Order By: Relevance
“…The survival data reported here not only confirm estimates from earlier reports, but also compare well with reports from other investigator‐initiated prospective and real‐world studies with ibrutinib in similar patient groups with high‐risk CLL. In a phase 2 study of single‐agent ibrutinib, investigators reported an estimated 24‐month PFS rate of 82% among patients with CLL and TP53 abnormalities, of whom 35 of 51 had previously untreated disease (Farooqui et al , 2015). Similarly, in a study combining ibrutinib and rituximab for patients with high‐risk CLL, a subgroup of mostly R/R patients with del(17p) or TP53 mutation had an 18‐month PFS rate that was 72% (Burger et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The survival data reported here not only confirm estimates from earlier reports, but also compare well with reports from other investigator‐initiated prospective and real‐world studies with ibrutinib in similar patient groups with high‐risk CLL. In a phase 2 study of single‐agent ibrutinib, investigators reported an estimated 24‐month PFS rate of 82% among patients with CLL and TP53 abnormalities, of whom 35 of 51 had previously untreated disease (Farooqui et al , 2015). Similarly, in a study combining ibrutinib and rituximab for patients with high‐risk CLL, a subgroup of mostly R/R patients with del(17p) or TP53 mutation had an 18‐month PFS rate that was 72% (Burger et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Ibrutinib is also tested in the frontline setting and has improved OS compared to chlorambucil in elderly patients [125]. Other trials of ibrutinibmainly comparison with ofatumumab (RESONATE) [95], combination with rituximab in high risk patients [97], combination with ofatumumab [98], in patients with TP53 mutations [96], with BR [99] Rai and Jain are summarized in Table III. CLL12 trial is first in kind trial as this trial will study ibrutinib in patients with early stage CLL who have high risk of progression depending upon the comprehensive prognostic index [126].…”
Section: Ibrutinibmentioning
confidence: 99%
“…17 More specifically, M-CLL cases treated with FCR in the context of clinical trials or general practice were independently reported to achieve prolonged responses, often with no detectable minimal residual disease, thus differing significantly from U-CLL cases. [18][19][20] Interestingly, upon treatment with newer therapeutic agents such as ibrutinib and idelalisib, CLL patients appear to benefit equally and experience similar overall responses irrespective of the IGHV mutational status; [21][22][23] however, the follow-up time is still limited thus precluding definitive conclusions. That said, differences have been noted between the two mutational groups regarding certain clinical parameters following the administration of novel drugs, for example, the initial ibrutinib-induced rise in lymphocyte count and also the duration of lymphocytosis is reported to be greater in M-CLL than that found in U-CLL patients.…”
Section: © Ferrata Storti Foundationmentioning
confidence: 99%
“…That said, differences have been noted between the two mutational groups regarding certain clinical parameters following the administration of novel drugs, for example, the initial ibrutinib-induced rise in lymphocyte count and also the duration of lymphocytosis is reported to be greater in M-CLL than that found in U-CLL patients. 21 While further investigations into the patterns of lymphocytosis and their association with a clinical response are warranted, these observations may hold value for follow-up assessment.…”
Section: © Ferrata Storti Foundationmentioning
confidence: 99%